The role of diet for the quality of life of lupus patients (Research, Society and Development, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory pathology that can affect any age and gender, but it manifests itself mainly in women of childbearing age, characterized by a period of disease activity and remission, where it can affect multiple organs and systems. The main focus of the present study is to address the importance of healthy eating for the quality of life of lupus patients. The methodology was descriptive research with a literature review approach, demonstrating through a bibliographic survey on the nutritional status and food consumption of patients with Systemic Lupus Erythematosus. In the results, in the majority of cases of lupus patients with obesity and overweight, and a higher incidence of the disease in women of childbearing age, low micronutrient intake was evidenced compared to what is recommended by the literature. It is concluded that overweight is frequent in SLE, and is related to food consumption and that it is more likely to develop metabolic and cardiovascular diseases, not only due to poor diet but also to the effects of corticosteroids and antimalarials, which also affect the patient's nutritional status.